Constitutional Court Of The Republic Of Indonesia: Safeguarding Citizens' Constitutional Rights In The Middle Of A Pandemic - Hani Adhani (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
International Seminar on Syariah and Law (INSLA 2020) E-Proceedings “Hala Tuju Syariah Dan Undang - Undang Mendepani Pandemik Covid - 19” Organized by : Faculty of Syariah and Law, Universiti Sains Islam Malaysia 27-28 October 2020